2014
DOI: 10.15288/jsad.2014.75.753
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alcohol Mixed With Energy Drinks as a Predictor of Alcohol-Related Consequences Two Years Later

Abstract: ABSTRACT. Objective:This study examines the use of alcohol mixed with energy drinks (AmED) as a predictor of alcohol problems and alcohol-related consequences and accidents two years later in a college student sample. Method: Longitudinal data on AmED use, alcohol consequences, and alcohol problems were collected from the fall of students' second year of college to the fall of their fourth year (N = 620, 49% male). Results: After we controlled for demographic indicators and heavy episodic drinking, AmED use wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Patrick, Evans‐Polce, & Maggs, conducted a prospective study to examine whether AMED consumption predicted alcohol‐related consequences 2 years later. They found that AMED consumption was associated with significantly increased AUDIT scores, greater alcohol intake, and corresponding negative consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Patrick, Evans‐Polce, & Maggs, conducted a prospective study to examine whether AMED consumption predicted alcohol‐related consequences 2 years later. They found that AMED consumption was associated with significantly increased AUDIT scores, greater alcohol intake, and corresponding negative consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research, mostly cross-sectional and American studies, has examined the possible negative effects of energy drink consumption among adolescents, including associations with the use of other substances, mainly alcohol (3)(4)(5)7,8,10,(14)(15)(16)(17)(18). On the one hand, energy drinks may act as a gateway for other addictive and risky behaviours and studies have shown that energy drinks may be the first experience in the substance use hierarchy (3,7,14).…”
Section: Key Notesmentioning
confidence: 99%
“…Although most studies do not investigate the direct interaction of TAU/EtOH, the combined used of EtOH and energy drinks is associated to major health problems. Thus, the combined use of alcohol and energy drinks increases the number and time of drinks consumed, dehydration, and more severe and prolonged hangovers, leading to an increase number of alcohol poisoning reports (Patrick et al 2014;Snipes and Benotsch 2013).…”
Section: Introductionmentioning
confidence: 99%